An Integrative Approach to Study the Inhibition of Providencia vermicola FabD Using C2-Quaternary Indolinones - Khataniar A; Das A; Baruah MJ; Bania KK; Rajkhowa S; Al-Hussain SA; Zaki ME (Dove Medical Press, 2023)
Ankita Khataniar,1,* Abhichandan Das,1,* Manash J Baruah,2 Kusum K Bania,2 Sanchaita Rajkhowa,1,* Sami A Al-Hussain,3 Magdi EA Zaki3 1Centre for Biotechnology and Bioinformatics, Dibrugarh University, Dibrugarh, As-786004, India; 2Department of Chemical Sciences, Tezpur University, Tezpur, As-784028, India; 3Department of Chemistry, Imam Mohammad Ibn Saud Islamic University (IMSIU), Riyadh, Saudi Arabia*These authors contributed equally to this workCorrespondence: Sanchaita Rajkhowa; Magdi EA Zaki, Email s_rajkhowa@dibru.ac.in; mezaki@imamu.edu.saBackground: The present study investigates the potential bioactivity of twelve experimentally designed C-2 quaternary indolinones against Providencia spp., a bacterial group of the Enterobacteriaceae family known to cause urinary tract infections. The study aims to provide insights into the bioactive properties of the investigated compounds and their potential use in developing novel treatments against Providencia spp. The experimental design of indolinones, combined with their unique chemical structure, makes them attractive candidates for further investigation. The results of this research may contribute to the development of novel therapeutic agents to combat Providencia spp. infections.Methods: The synthesized indolinones (moL1-moL12) are evaluated to identify any superior activity, particularly focusing on moL12, which possesses aza functionality. The antimicrobial activities of all twelve compounds are tested in triplicates against six different Gram-positive and Gram-negative organisms, including P. vermicola (P< 0.05). Computational methods have been employed to assess the pharmacokinetic properties of the compounds.Results: Among the synthesized indolinones, moL12 exhibits superior activity compared to the other compounds with similar skeleton but different functional moieties. All six strains tested, including P. vermicola, demonstrated sensitivity to moL12. Computational studies support the pharmacokinetic properties of moL12, indicating acceptable absorption, distribution, metabolism, excretion, and toxicity characteristics.Conclusion: Utilizing the PPI approach, we have identified a promising target, FabD, in Gram-negative bacteria. Our analysis has shown that moL12 exhibits significant potential in binding with FabD, thereby, might inhibit cell wall formation, and display superior antimicrobial activity compared to other compounds. Consequently, moL12 may be a potential therapeutic agent that could be used to combat urinary tract infections caused by Providencia spp. The findings of this research hold significant promise for the development of new and effective treatments for bacterial infections. Keywords: C-2 quaternary indolinones, Providencia vermicola, Providencia stuartii, multi-drug resistance, molecular docking, molecular dynamics simulation